Quantitative revolution 2 : the critical (re)turn - Kwan, M; Schwanen, T (Routledge, 2009)
Although many have questioned the adequacy of quantitative methods for addressing issues of concern in critical geographies, such as social justice and inequality, many have argued that quantification can potentially make rich contributions to understanding and addressing these issues. In light of the recent attempts to reassert the critical potential and positive role of quantitative geography, we suggest in this introductory article for the Focus Section that the antagonism between critical and quantitative geographies is not beneficial to the discipline. We highlight some promising developments in modern quantitative geography and reflect on the ways in which the critical–quantitative binary can be at least partially eclipsed. We emphasize that knowledge in quantitative methods is essential for deciphering and challenging regressive political agendas, now often supported by numbers and quantitative analysis. Quantitative geography, when integrated with a critical sensibility and used appropriately, can be a powerful tool for fostering progressive social and political change.